BIONEENSIS BIOLOGICAL FERTILIZER DISTRIBUTION ANALYSIS IN THE SUMATERA ISLAND REGION - Fahri Putra Hafira; Abdul Rauf; Isfenti Sadalia (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
The title of this study is "Analysis of Bioneensis Biofertilizer Distribution in the Sumatra Island Region". This type of research is a qualitative analytical research with a case study design. The number of informants in this study was 27 informants. The results of the research that has been conducted indicate that the distribution process of biofertilizers in the Sumatra Island Region has been carried out in accordance with the distribution procedures that have been set by the company which is done by increasing the number of Marketing Partners in each Province that are legally registered so that their legality is clear which will be used to facilitate or bring the distribution of Bioneensis biofertilizers closer to users. The problem concerning the smooth distribution process of Bioneensis biofertilizers in the Sumatra Island Region at the distributor is the limited transportation to distribute Bioneensis biofertilizers to resellers where limited transportation or transportation results in expensive shipping costs and also shipping times that take quite a long time, and there are also obstacles regarding errors in reporting verification results and validation as well as in the payment system that uses cashless. For the obstacles faced by resellers in the process of distributing Bioneensis biofertilizer to farmers in the Sumatra Island Region, it also lies in shipping where shipping costs from distributors are expensive, competition between resellers is increasing, and also in the shipping process where there are still many areas that are still difficult to access by couriers which will cause limited fertilizer stock among resellers to be distributed to farmers. Suggestions for further researchers It is suggested to further develop the research model, add discussion topics such as obstacles in carrying out distribution and also how to overcome them so that in the future research on the distribution of Bioneensis biofertilizer can be more varied and better.